The German adaptation of the Cambridge pulmonary hypertension outcome review (CAMPHOR) - Cima Katharina (Health and Quality of Life Outcomes, 2012)
Abstract Background Individuals with precapillary pulmonary hypertension (PH) experience severely impaired quality of life. A disease-specific outcome measure for PH, the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) was developed and validated in the UK and subsequently adapted for use in additional countries. The aim of this study was to translate and assess the reliability and validity of the CAMPHOR for German-speaking populations. Methods Three main adaptation stages involved; translation (employing bilingual and lay panels), cognitive debriefing interviews with patients and validation (assessment of the adaptation’s psychometric properties). The psychometric evaluation included 107 patients with precapillary PH (60 females; age mean (standard deviation) 60 (15) years) from 3 centres in Austria, Germany and Switzerland. Results No major problems were found with the translation process with most items easily rendered into acceptable German. Participants in the cognitive debriefing interviews found the questionnaires relevant, comprehensive and easy to complete. Psychometric analyses showed that the adaptation was successful. The three CAMPHOR scales (symptoms, activity limitations and quality of life) had excellent test-retest reliability correlations (Symptoms = 0.91; Activity limitations = 0.91; QoL = 0.90) and internal consistency (Symptoms = 0.94; Activity limitations = 0.93; QoL = 0.94). Predicted correlations with the Nottingham Health Profile provided evidence of the construct validity of the CAMPHOR scales. The CAMPHOR adaptation also showed known group validity in its ability to distinguish between participants based on perceived general health, perceived disease severity, oxygen use and NYHA classification. Conclusions The CAMPHOR has been shown to be valid and reliable in the German population and is recommend for use in clinical practice.